FOLK ART IS A COMPREHENSIVE TOOL FOR DEVELOPING CHILDREN (Konferensiyalar | Conferences, 2024)
The article explores the importance of oral Kazakh folk literature in the development, cognitive growth, and education of preschool children. The ability of children to express their thoughts through artistic means such as fairy tales, riddles, proverbs, and sayings is assessed, along with their understanding and comparison of these works. Since folk traditions are the sole cultural heritage of the country in terms of history, culture, art, and economics, it is crucial to enhance the scientific and pedagogical justification for preschoolers in accordance with the demands of modern society.